Question
upstudy study bank question image url

EXERCISE 11 Solve simultaneously for \( x \) and \( y \) in each equatio \( 1 y=3 x^{2}-2 x-8 \) and \( y=5 x-2 \) \( 2 y=-5 x^{2}+4 x+9 \) and \( y+6 x=9 \) \( 3 y=\frac{3}{4} x^{2}+12 \) and \( 3 x+2 y=12 \) \( 4 \quad y=-\frac{1}{2} x^{2}-\frac{1}{2} x+6 \) and \( x+2 y=8 \) \( 5 \quad y=-\frac{1}{2}(x-1)(x+6) \) and \( 2 x+5 y=5 \) \( 6, y=x^{2}-5 x+4 \) and \( y-2 x+6=0 \) \( 7 \quad y=-x^{2}-5 x+6 \) and \( y=\frac{1}{2}(x+1)^{2}-2 \) \( 8 \quad y=(x-2)^{2}-3 \) and \( y=-\frac{1}{2}(x-5)^{2}+6 \) \( 9 y=-x^{2}-x+4 \) and \( y=2(x-1)^{2}-4 \)

Ask by Howell Ortega. in South Africa
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Here are the solutions for each pair of equations: 1. \( y = 3x^2 - 2x - 8 \) and \( y = 5x - 2 \): - Solutions: \( (-\frac{2}{3}, -\frac{16}{3}) \) and \( (3, 13) \). 2. \( y = -5x^2 + 4x + 9 \) and \( y + 6x = 9 \): - Solutions: \( (0, 9) \) and \( (2, -3) \). 3. \( y = \frac{3}{4}x^2 + 12 \) and \( 3x + 2y = 12 \): - No real solutions. 4. \( y = -\frac{1}{2}x^2 - \frac{1}{2}x + 6 \) and \( x + 2y = 8 \): - Solutions: \( (-2, 5) \) and \( (2, 3) \). 5. \( y = -\frac{1}{2}(x-1)(x+6) \) and \( 2x + 5y = 5 \): - Solutions: \( (-5, 3) \) and \( \left(\frac{4}{5}, \frac{17}{25}\right) \). 6. \( y = x^2 - 5x + 4 \) and \( y - 2x + 6 = 0 \): - Solutions: \( (2, -2) \) and \( (5, 4) \). 7. \( y = -x^2 - 5x + 6 \) and \( y = \frac{1}{2}(x+1)^2 - 2 \): - Solutions: \( (-5, 6) \) and \( (1, 0) \). 8. \( y = (x-2)^2 - 3 \) and \( y = -\frac{1}{2}(x-5)^2 + 6 \): - Solutions: \( (1, -2) \) and \( (5, 6) \). 9. \( y = -x^2 - x + 4 \) and \( y = 2(x-1)^2 - 4 \): - Solutions: \( (-1, 4) \) and \( (2, -2) \). If you need more help with any specific pair, let me know!

Solution

Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y=x^{2}-5x+4\\y-2x+6=0\end{array}\right.\) - step1: Substitute the value of \(y:\) \(x^{2}-5x+4-2x+6=0\) - step2: Simplify: \(x^{2}-7x+10=0\) - step3: Factor the expression: \(\left(x-5\right)\left(x-2\right)=0\) - step4: Separate into possible cases: \(\begin{align}&x-5=0\\&x-2=0\end{align}\) - step5: Solve the equation: \(\begin{align}&x=5\\&x=2\end{align}\) - step6: Calculate: \(x=5\cup x=2\) - step7: Rearrange the terms: \(\left\{ \begin{array}{l}x=5\\y=x^{2}-5x+4\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=x^{2}-5x+4\end{array}\right.\) - step8: Calculate: \(\left\{ \begin{array}{l}x=5\\y=4\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=-2\end{array}\right.\) - step9: Calculate: \(\left\{ \begin{array}{l}x=2\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=5\\y=4\end{array}\right.\) - step10: Check the solution: \(\left\{ \begin{array}{l}x=2\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=5\\y=4\end{array}\right.\) - step11: Rewrite: \(\left(x,y\right) = \left(2,-2\right)\cup \left(x,y\right) = \left(5,4\right)\) Solve the system of equations \( y=-\frac{1}{2} x^{2}-\frac{1}{2} x+6;x+2 y=8 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y=-\frac{1}{2}x^{2}-\frac{1}{2}x+6\\x+2y=8\end{array}\right.\) - step1: Substitute the value of \(y:\) \(x+2\left(-\frac{1}{2}x^{2}-\frac{1}{2}x+6\right)=8\) - step2: Simplify: \(-x^{2}+12=8\) - step3: Move the constant to the right side: \(-x^{2}=8-12\) - step4: Subtract the numbers: \(-x^{2}=-4\) - step5: Change the signs: \(x^{2}=4\) - step6: Simplify the expression: \(x=\pm \sqrt{4}\) - step7: Simplify: \(x=\pm 2\) - step8: Separate into possible cases: \(x=2\cup x=-2\) - step9: Rearrange the terms: \(\left\{ \begin{array}{l}x=2\\y=-\frac{1}{2}x^{2}-\frac{1}{2}x+6\end{array}\right.\cup \left\{ \begin{array}{l}x=-2\\y=-\frac{1}{2}x^{2}-\frac{1}{2}x+6\end{array}\right.\) - step10: Calculate: \(\left\{ \begin{array}{l}x=2\\y=3\end{array}\right.\cup \left\{ \begin{array}{l}x=-2\\y=5\end{array}\right.\) - step11: Calculate: \(\left\{ \begin{array}{l}x=-2\\y=5\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=3\end{array}\right.\) - step12: Check the solution: \(\left\{ \begin{array}{l}x=-2\\y=5\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=3\end{array}\right.\) - step13: Rewrite: \(\left(x,y\right) = \left(-2,5\right)\cup \left(x,y\right) = \left(2,3\right)\) Solve the system of equations \( y=-5 x^{2}+4 x+9;y+6 x=9 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y=-5x^{2}+4x+9\\y+6x=9\end{array}\right.\) - step1: Substitute the value of \(y:\) \(-5x^{2}+4x+9+6x=9\) - step2: Add the terms: \(-5x^{2}+10x+9=9\) - step3: Cancel equal terms: \(-5x^{2}+10x=0\) - step4: Factor the expression: \(-5x\left(x-2\right)=0\) - step5: Separate into possible cases: \(\begin{align}&-5x=0\\&x-2=0\end{align}\) - step6: Solve the equation: \(\begin{align}&x=0\\&x=2\end{align}\) - step7: Calculate: \(x=0\cup x=2\) - step8: Rearrange the terms: \(\left\{ \begin{array}{l}x=0\\y=-5x^{2}+4x+9\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=-5x^{2}+4x+9\end{array}\right.\) - step9: Calculate: \(\left\{ \begin{array}{l}x=0\\y=9\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=-3\end{array}\right.\) - step10: Check the solution: \(\left\{ \begin{array}{l}x=0\\y=9\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=-3\end{array}\right.\) - step11: Rewrite: \(\left(x,y\right) = \left(0,9\right)\cup \left(x,y\right) = \left(2,-3\right)\) Solve the system of equations \( y=-x^{2}-x+4;y=2(x-1)^{2}-4 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y=-x^{2}-x+4\\y=2\left(x-1\right)^{2}-4\end{array}\right.\) - step1: Substitute the value of \(y:\) \(-x^{2}-x+4=2\left(x-1\right)^{2}-4\) - step2: Simplify: \(-x^{2}-x+4=2x^{2}-4x-2\) - step3: Move the expression to the left side: \(-x^{2}-x+4-\left(2x^{2}-4x-2\right)=0\) - step4: Calculate: \(-3x^{2}+3x+6=0\) - step5: Factor the expression: \(-3\left(x-2\right)\left(x+1\right)=0\) - step6: Divide the terms: \(\left(x-2\right)\left(x+1\right)=0\) - step7: Separate into possible cases: \(\begin{align}&x-2=0\\&x+1=0\end{align}\) - step8: Solve the equation: \(\begin{align}&x=2\\&x=-1\end{align}\) - step9: Calculate: \(x=2\cup x=-1\) - step10: Rearrange the terms: \(\left\{ \begin{array}{l}x=2\\y=-x^{2}-x+4\end{array}\right.\cup \left\{ \begin{array}{l}x=-1\\y=-x^{2}-x+4\end{array}\right.\) - step11: Calculate: \(\left\{ \begin{array}{l}x=2\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=-1\\y=4\end{array}\right.\) - step12: Calculate: \(\left\{ \begin{array}{l}x=-1\\y=4\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=-2\end{array}\right.\) - step13: Check the solution: \(\left\{ \begin{array}{l}x=-1\\y=4\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=-2\end{array}\right.\) - step14: Rewrite: \(\left(x,y\right) = \left(-1,4\right)\cup \left(x,y\right) = \left(2,-2\right)\) Solve the system of equations \( y=3 x^{2}-2 x-8;y=5 x-2 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y=3x^{2}-2x-8\\y=5x-2\end{array}\right.\) - step1: Substitute the value of \(y:\) \(3x^{2}-2x-8=5x-2\) - step2: Move the expression to the left side: \(3x^{2}-2x-8-\left(5x-2\right)=0\) - step3: Subtract the terms: \(3x^{2}-7x-6=0\) - step4: Factor the expression: \(\left(x-3\right)\left(3x+2\right)=0\) - step5: Separate into possible cases: \(\begin{align}&x-3=0\\&3x+2=0\end{align}\) - step6: Solve the equation: \(\begin{align}&x=3\\&x=-\frac{2}{3}\end{align}\) - step7: Calculate: \(x=3\cup x=-\frac{2}{3}\) - step8: Rearrange the terms: \(\left\{ \begin{array}{l}x=3\\y=3x^{2}-2x-8\end{array}\right.\cup \left\{ \begin{array}{l}x=-\frac{2}{3}\\y=3x^{2}-2x-8\end{array}\right.\) - step9: Calculate: \(\left\{ \begin{array}{l}x=3\\y=13\end{array}\right.\cup \left\{ \begin{array}{l}x=-\frac{2}{3}\\y=-\frac{16}{3}\end{array}\right.\) - step10: Calculate: \(\left\{ \begin{array}{l}x=-\frac{2}{3}\\y=-\frac{16}{3}\end{array}\right.\cup \left\{ \begin{array}{l}x=3\\y=13\end{array}\right.\) - step11: Check the solution: \(\left\{ \begin{array}{l}x=-\frac{2}{3}\\y=-\frac{16}{3}\end{array}\right.\cup \left\{ \begin{array}{l}x=3\\y=13\end{array}\right.\) - step12: Rewrite: \(\left(x,y\right) = \left(-\frac{2}{3},-\frac{16}{3}\right)\cup \left(x,y\right) = \left(3,13\right)\) Solve the system of equations \( y=\frac{3}{4} x^{2}+12;3 x+2 y=12 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y=\frac{3}{4}x^{2}+12\\3x+2y=12\end{array}\right.\) - step1: Substitute the value of \(y:\) \(3x+2\left(\frac{3}{4}x^{2}+12\right)=12\) - step2: Expand the expression: \(3x+\frac{3}{2}x^{2}+24=12\) - step3: Move the expression to the left side: \(3x+\frac{3}{2}x^{2}+24-12=0\) - step4: Subtract the numbers: \(3x+\frac{3}{2}x^{2}+12=0\) - step5: Rewrite in standard form: \(\frac{3}{2}x^{2}+3x+12=0\) - step6: Multiply both sides: \(2\left(\frac{3}{2}x^{2}+3x+12\right)=2\times 0\) - step7: Calculate: \(3x^{2}+6x+24=0\) - step8: Solve using the quadratic formula: \(x=\frac{-6\pm \sqrt{6^{2}-4\times 3\times 24}}{2\times 3}\) - step9: Simplify the expression: \(x=\frac{-6\pm \sqrt{6^{2}-4\times 3\times 24}}{6}\) - step10: Simplify the expression: \(x=\frac{-6\pm \sqrt{-252}}{6}\) - step11: The expression is undefined: \(x \notin \mathbb{R}\) - step12: The system of equations has no solution in the set of real numbers: \(\left(x,y\right) \notin \mathbb{R}^{2}\) - step13: Alternative Form: \(\textrm{No real solution}\) Solve the system of equations \( y=-\frac{1}{2}(x-1)(x+6);2 x+5 y=5 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y=-\frac{1}{2}\left(x-1\right)\left(x+6\right)\\2x+5y=5\end{array}\right.\) - step1: Calculate: \(\left\{ \begin{array}{l}y=\left(-\frac{1}{2}x+\frac{1}{2}\right)\left(x+6\right)\\2x+5y=5\end{array}\right.\) - step2: Substitute the value of \(y:\) \(2x+5\left(-\frac{1}{2}x+\frac{1}{2}\right)\left(x+6\right)=5\) - step3: Simplify: \(-\frac{21}{2}x-\frac{5}{2}x^{2}+15=5\) - step4: Move the expression to the left side: \(-\frac{21}{2}x-\frac{5}{2}x^{2}+15-5=0\) - step5: Subtract the numbers: \(-\frac{21}{2}x-\frac{5}{2}x^{2}+10=0\) - step6: Factor the expression: \(\frac{1}{2}\left(-x-5\right)\left(5x-4\right)=0\) - step7: Divide the terms: \(\left(-x-5\right)\left(5x-4\right)=0\) - step8: Separate into possible cases: \(\begin{align}&-x-5=0\\&5x-4=0\end{align}\) - step9: Solve the equation: \(\begin{align}&x=-5\\&x=\frac{4}{5}\end{align}\) - step10: Calculate: \(x=-5\cup x=\frac{4}{5}\) - step11: Rearrange the terms: \(\left\{ \begin{array}{l}x=-5\\y=\left(-\frac{1}{2}x+\frac{1}{2}\right)\left(x+6\right)\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{4}{5}\\y=\left(-\frac{1}{2}x+\frac{1}{2}\right)\left(x+6\right)\end{array}\right.\) - step12: Calculate: \(\left\{ \begin{array}{l}x=-5\\y=3\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{4}{5}\\y=\frac{17}{25}\end{array}\right.\) - step13: Check the solution: \(\left\{ \begin{array}{l}x=-5\\y=3\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{4}{5}\\y=\frac{17}{25}\end{array}\right.\) - step14: Rewrite: \(\left(x,y\right) = \left(-5,3\right)\cup \left(x,y\right) = \left(\frac{4}{5},\frac{17}{25}\right)\) Solve the system of equations \( y=-x^{2}-5 x+6;y=\frac{1}{2}(x+1)^{2}-2 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y=-x^{2}-5x+6\\y=\frac{1}{2}\left(x+1\right)^{2}-2\end{array}\right.\) - step1: Substitute the value of \(y:\) \(-x^{2}-5x+6=\frac{1}{2}\left(x+1\right)^{2}-2\) - step2: Simplify: \(-x^{2}-5x+6=\frac{1}{2}x^{2}+x-\frac{3}{2}\) - step3: Move the expression to the left side: \(-x^{2}-5x+6-\left(\frac{1}{2}x^{2}+x-\frac{3}{2}\right)=0\) - step4: Calculate: \(-\frac{3}{2}x^{2}-6x+\frac{15}{2}=0\) - step5: Factor the expression: \(-\frac{3}{2}\left(x-1\right)\left(x+5\right)=0\) - step6: Divide the terms: \(\left(x-1\right)\left(x+5\right)=0\) - step7: Separate into possible cases: \(\begin{align}&x-1=0\\&x+5=0\end{align}\) - step8: Solve the equation: \(\begin{align}&x=1\\&x=-5\end{align}\) - step9: Calculate: \(x=1\cup x=-5\) - step10: Rearrange the terms: \(\left\{ \begin{array}{l}x=1\\y=-x^{2}-5x+6\end{array}\right.\cup \left\{ \begin{array}{l}x=-5\\y=-x^{2}-5x+6\end{array}\right.\) - step11: Calculate: \(\left\{ \begin{array}{l}x=1\\y=0\end{array}\right.\cup \left\{ \begin{array}{l}x=-5\\y=6\end{array}\right.\) - step12: Calculate: \(\left\{ \begin{array}{l}x=-5\\y=6\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\y=0\end{array}\right.\) - step13: Check the solution: \(\left\{ \begin{array}{l}x=-5\\y=6\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\y=0\end{array}\right.\) - step14: Rewrite: \(\left(x,y\right) = \left(-5,6\right)\cup \left(x,y\right) = \left(1,0\right)\) Solve the system of equations \( y=(x-2)^{2}-3;y=-\frac{1}{2}(x-5)^{2}+6 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y=\left(x-2\right)^{2}-3\\y=-\frac{1}{2}\left(x-5\right)^{2}+6\end{array}\right.\) - step1: Substitute the value of \(y:\) \(\left(x-2\right)^{2}-3=-\frac{1}{2}\left(x-5\right)^{2}+6\) - step2: Simplify: \(\left(x-2\right)^{2}-3=-\frac{1}{2}x^{2}+5x-\frac{13}{2}\) - step3: Move the expression to the left side: \(\left(x-2\right)^{2}-3-\left(-\frac{1}{2}x^{2}+5x-\frac{13}{2}\right)=0\) - step4: Subtract the terms: \(\left(x-2\right)^{2}+\frac{7}{2}+\frac{1}{2}x^{2}-5x=0\) - step5: Calculate: \(\frac{3}{2}x^{2}-9x+\frac{15}{2}=0\) - step6: Factor the expression: \(\frac{3}{2}\left(x-5\right)\left(x-1\right)=0\) - step7: Divide the terms: \(\left(x-5\right)\left(x-1\right)=0\) - step8: Separate into possible cases: \(\begin{align}&x-5=0\\&x-1=0\end{align}\) - step9: Solve the equation: \(\begin{align}&x=5\\&x=1\end{align}\) - step10: Calculate: \(x=5\cup x=1\) - step11: Rearrange the terms: \(\left\{ \begin{array}{l}x=5\\y=\left(x-2\right)^{2}-3\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\y=\left(x-2\right)^{2}-3\end{array}\right.\) - step12: Calculate: \(\left\{ \begin{array}{l}x=5\\y=6\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\y=-2\end{array}\right.\) - step13: Calculate: \(\left\{ \begin{array}{l}x=1\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=5\\y=6\end{array}\right.\) - step14: Check the solution: \(\left\{ \begin{array}{l}x=1\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=5\\y=6\end{array}\right.\) - step15: Rewrite: \(\left(x,y\right) = \left(1,-2\right)\cup \left(x,y\right) = \left(5,6\right)\) Here are the solutions for each pair of equations: 1. For the equations \( y = 3x^2 - 2x - 8 \) and \( y = 5x - 2 \): - The solutions are \( (x,y) = \left(-\frac{2}{3}, -\frac{16}{3}\right) \) and \( (x,y) = (3, 13) \). 2. For the equations \( y = -5x^2 + 4x + 9 \) and \( y + 6x = 9 \): - The solutions are \( (x,y) = (0, 9) \) and \( (x,y) = (2, -3) \). 3. For the equations \( y = \frac{3}{4}x^2 + 12 \) and \( 3x + 2y = 12 \): - There are no real solutions. 4. For the equations \( y = -\frac{1}{2}x^2 - \frac{1}{2}x + 6 \) and \( x + 2y = 8 \): - The solutions are \( (x,y) = (-2, 5) \) and \( (x,y) = (2, 3) \). 5. For the equations \( y = -\frac{1}{2}(x-1)(x+6) \) and \( 2x + 5y = 5 \): - The solutions are \( (x,y) = (-5, 3) \) and \( (x,y) = \left(\frac{4}{5}, \frac{17}{25}\right) \). 6. For the equations \( y = x^2 - 5x + 4 \) and \( y - 2x + 6 = 0 \): - The solutions are \( (x,y) = (2, -2) \) and \( (x,y) = (5, 4) \). 7. For the equations \( y = -x^2 - 5x + 6 \) and \( y = \frac{1}{2}(x+1)^2 - 2 \): - The solutions are \( (x,y) = (-5, 6) \) and \( (x,y) = (1, 0) \). 8. For the equations \( y = (x-2)^2 - 3 \) and \( y = -\frac{1}{2}(x-5)^2 + 6 \): - The solutions are \( (x,y) = (1, -2) \) and \( (x,y) = (5, 6) \). 9. For the equations \( y = -x^2 - x + 4 \) and \( y = 2(x-1)^2 - 4 \): - The solutions are \( (x,y) = (-1, 4) \) and \( (x,y) = (2, -2) \). If you need further assistance or explanations for any specific pair, feel free to ask!

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

Solving simultaneous equations isn't just about finding \( x \) and \( y \); it's like playing detective with numbers! Let's take the first set of equations, \( y = 3x^2 - 2x - 8 \) and \( y = 5x - 2 \). By substituting \( 5x - 2 \) into the first equation, we can unravel the mystery of \( x \) and then find \( y \) like a math magician pulling rabbits out of hats! Now for some real-world applications: solving simultaneous equations can help when you're balancing budgets or optimizing production in factories! Think of it as a mathematical tool to devise the best plans, whether you're cooking up a recipe with just the right ingredients or managing resources in a business. The beauty is, once you master it, you'll see it everywhere—turning complexity into clarity!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy